FUNCTIONAL OUTCOME OF PATIENTS WITH OSTEOARTHRITIS KNEE TREATED BY INTRAARTICULAR INJECTIONS OF PLATELET-RICH PLASMA - VIKAS KUNTWAD; PRAMOD PRALHAD TUPE; AMOL WAGH (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: The aims and objectives of the study are (1) to assess pain relief and functional outcome in knee osteoarthritis (OA) cases treated by intra-articular injection of platelet-rich plasma (PRP) and (2) to study the complication in patients treated by intra-articular injection of PRP. Methods: This was a prospective study conducted in the department of orthopedics of a tertiary care medical institute. 60 patients with Grade 2 and Grade 3 OA of knee were included in this study on the basis of a pre-defined inclusion and exclusion criteria. All patients were treated by intra-articular injection of PRP. Patients were followed up for 6 months. During follow-up visits, assessment of severity of pain and functional outcome was done by Visual Analog Scale (VAS) Score and Japanese Orthopedic Association (JOA) Score. Patients were also assessed for complications. p<0.05 was taken as statistically significant. Results: Out of 60 studied cases, there was a female preponderance with a M: F ratio of 1:0.62. The mean age of affected cases was found to be 65.84±11.86 years and mean duration of symptoms was found to be 2.52±1.26 years. Majority of the patients were either overweight (45.00%) or obese (36.67%) and only 11 (18.33%) patients had a healthy weight. 38 (63.33%) patients were having Grade 3 OA whereas 22 (36.67%) patients were having Grade 2 OA. There was a significant reduction in pain and significant functional improvement at the time of final follow-up as compared to VAS and JOA scores at the time of presentation (p<0.0001). Complications were seen in any of the cases. Conclusion: Patients with Grade 2 and Grade 3 OA of knee treated by intra-articular injection of PRP show excellent outcome in terms of pain relief and functional outcome with no significant complications.